(3fXQjGJ(B- (3feGPL(B- (3GSJQGJjLjGJs - (3GSeGYjd eMeO(B, (3Hf bGfIs ((3YeGf(B:s (3OGQ CSGeI ddfTQ hGdJhRjY(B,s, 2011)
(3EbJUGO GdJfejI, GdeaGgje hHOGjGJ GdEgJeGe GdChdi(B- (3fXQjGJ GdJfejI hfeGPL Gdfeh(B- (3NjGQGJ GdJfejI hJMhd eaghegG aj GdacQ GdEbJUGOj GdeYGUQ(B- (3GdeTcdGJ hGdSjGSGJ GdJfehjI(B- (3Jehjd hJNWjW GdJfejI GdEbJUGOjIs
Keywords: (3GdEbJUGO GdJfejIs; (3GdJfejI GdELJeGYjIs; (3GdJfejI GdEbJUGOjIs